PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN DENGAN SELERA SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Perusahaan Daerah Pasar Horas Jaya Pematangsiantar) - Mega Romauly Tampubolon; Sumaizar Sumaizar (Politeknik Bisnis Indonesia, 2020)
`Abstarct The development of the times is growing rapidly marked by increasingly sophisticated technology. The formulation of the problem in this study is how the influence of prices on purchasing decisions with taste as an intervening variable. This research aims to determine the price of purchasing decisions with taste as an intervening variable. The research design used by the author is field research, where the research was conducted at the Pematangsiantar Horas Jaya Regional Corporation, the population that is the Sword in the Horas Market in the Horas Regional Company. The sampling technique uses purposive sampling with the criteria of shoe traders as a research sample of 56 traders. Data analysis techniques using simple regression, hypothesis testing, coefficient of determination, and path analysis. The results of the study showed that the price had a positive and significant influence on purchasing decisions in the Regional Corporation of Horas Jaya, Pematangsiantar City, and taste was an intervening variable, or by adding a variable of tastes the price effect on purchasing decisions was higher.